(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
The main objective of macroeconomic policy is to maintain macroeconomic equilibrium by achieving the main macroeconomic goals. These goals can be represented by the desire to maintain stable growth in national output and stable price levels. But an equally important macroeconomic goal is to achieve a high level of employment. This article is devoted to the issues of increasing employment in Uzbekistan in the context of modern economic development of the republic. The article systematizes the theoretical and methodological approaches to the category of "employment" and discusses its relationship with macroeconomic growth and demographic factors. In addition, a retrospective analysis of the development of the labor market and employment has been conducted in this article. In accordance with the development strategy of new Uzbekistan for 2022-2026, the main directions of further development of employment.